ANALISIS PERSEPSI KONSUMEN TERHADAP BAURAN PROMOSI PADA MATAHARI DEPARTMENT STORE GTC TANJUNG BUNGA MAKASSAR - Jam'ah, Andi; Asdar, Asdar; Karim, Ayu (Perpustakaan dan Penerbitan Unismuh Makassar, 2017)
This research is done by quantitative analysis method. This method is done by comparing Consumer Perceptions Against Promotion Mix On Sun Department Store GTC Tanjug Bunga Makassar. Data Collection by Observation Method and Questionnaire Questionnaire. The results of the study concluded that (i) jikavariabel Advertising, Sales Promotion, Public Relations and Publicity, Personal Selling, and Dirrect Marketing tested both partially and simultaneously affect the Promotion Mix On Matahari Department Store GTC Tanjung Bunga Makassar, the most influential Dominant variable is Dirrect Marketing (Marketing Direct) has a value of t arithmetic (11,685)> t table (1.986) the largest compared with other variables, with significant 0.05